SOME CONSIDERATIONS ON VEGETABLES AND TOMATOES PRODUCTION AND CONSUMPTION IN ROMANIA IN THE PERIOD 2007-2014 - Agatha POPESCU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The purpose of the paper was to analyze vegetables and mainly tomatoes contribution to fruit production and consumption in Romania. Based on the statistical data for the period 2007-2014, it was studied the dynamics of the surface cultivated with vegetables and tomatoes, vegetable and tomatoes production, tomatoes yield, vegetable and tomatoes production per inhabitant, and also consumption and producer's price. Although vegetable and tomatoes cultivated area declined by 22 %, and respectively by 10 %, vegetable production reached 3,808 thousand tons and tomatoes production 711 thousand tons in 2014. For this reason, Romania comes on the 8th position among the top tomatoes producers in the EU-28. The vegetable intake of 186 kg and tomatoes consumption of 38 kg per capita and year, Romania exceeds WHO's recommendations assuring a healthy offer to its inhabitants. Tomatoes are a top vegetable contributing by 18.3 % to the cultivated area with vegetables and by 18.9 % to vegetable production. But, tomatoes yield of 15.1 tons per ha in 2014 is still small compared to other top producers. And tomatoes price at farm gate is Euro 73/100 kg much higher than in other countries. For this reason, to increase productivity and efficiency along the product chain, it is needed to extend tomatoes growing in green houses by investing in modern farms where modern technologies to be implemented. Producers must join their capital and efforts into an associative forms, to enlarge farm size for getting cheaper farm inputs, for applying modern technologies, for better selling their products. An EU financial support is required, but the EU criteria should be revised and much better tailored to the concrete conditions of Romania's small holdings, which are the most numerous in the Community.